Question
upstudy study bank question image url

\( \left. \begin{array} { l } { x = \sqrt { 3 } - 2 } \\ { y = \sqrt { 3 } - 1 } \end{array} \right\} \Rightarrow \sqrt[ 4 ] { x ^ { 4 } } + \sqrt { ( x - y ) ^ { 2 } } = ? \)

Ask by Graham Chambers. in Turkey
Feb 17,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Natija: \( 3 - \sqrt{3} \).

Solution

Berilgan tenglamalar: \[ \begin{array} { l } { x = \sqrt { 3 } - 2 } \\ { y = \sqrt { 3 } - 1 } \end{array} \] Bizga quyidagi ifodani hisoblash kerak: \[ \sqrt[4]{x^4} + \sqrt{(x - y)^2} \] 1. **Birinchi qadam:** \( \sqrt[4]{x^4} \) ni hisoblaymiz. Bu ifoda \( |x| \) ga teng, chunki \( \sqrt[4]{x^4} = |x| \). 2. **Ikkinchi qadam:** \( x \) ni hisoblaymiz: \[ x = \sqrt{3} - 2 \] \( \sqrt{3} \) taxminan 1.732 ga teng, shuning uchun: \[ x \approx 1.732 - 2 = -0.268 \] Demak, \( |x| = -x = 2 - \sqrt{3} \). 3. **Uchinchi qadam:** \( y \) ni hisoblaymiz: \[ y = \sqrt{3} - 1 \approx 1.732 - 1 = 0.732 \] 4. **To'rtinchi qadam:** \( x - y \) ni hisoblaymiz: \[ x - y = (\sqrt{3} - 2) - (\sqrt{3} - 1) = -2 + 1 = -1 \] Shunday qilib, \( (x - y)^2 = (-1)^2 = 1 \). 5. **Beshinchi qadam:** Endi ifodani to'liq hisoblaymiz: \[ \sqrt[4]{x^4} + \sqrt{(x - y)^2} = |x| + \sqrt{1} = (2 - \sqrt{3}) + 1 \] 6. **Oltinchi qadam:** Natijani hisoblaymiz: \[ 2 - \sqrt{3} + 1 = 3 - \sqrt{3} \] Shunday qilib, natija: \[ \sqrt[4]{x^4} + \sqrt{(x - y)^2} = 3 - \sqrt{3} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let's first simplify the expressions \(x\) and \(y\): 1. \(x = \sqrt{3} - 2\) 2. \(y = \sqrt{3} - 1\) Now we need to calculate: \(\sqrt[4]{x^4} + \sqrt{(x - y)^2}\) Starting with \(\sqrt[4]{x^4}\): \[ \sqrt[4]{x^4} = |x| \] Now calculate \(|x|\): Since \(x = \sqrt{3} - 2 \) and \(\sqrt{3} \approx 1.732\), we find: \[ \sqrt{3} - 2 \approx 1.732 - 2 = -0.268 \] Thus, \(|x| = -x = 2 - \sqrt{3}\). Next, we calculate \(x - y\): \[ x - y = (\sqrt{3} - 2) - (\sqrt{3} - 1) = -2 + 1 = -1 \] Then, we need \(\sqrt{(x - y)^2}\): \[ \sqrt{(x - y)^2} = |x - y| = |-1| = 1 \] Putting it all together: \[ \sqrt[4]{x^4} + \sqrt{(x - y)^2} = |x| + |x - y| = (2 - \sqrt{3}) + 1 = 3 - \sqrt{3} \] Therefore, the final answer is: \[ 3 - \sqrt{3} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy